[Translated article] Mpox - Formerly Monkey Pox - in Dermatology: A Review of Epidemiologic Features, Clinical Presentation, Diagnosis, and Treatment - A. Catala; J. Riera; I. Fuertes (Elsevier, 2023)
Mpox is an emerging zoonotic disease that has spread rapidly around the world. It has been declared a public health emergency of international concern by the World Health Organization. This review is an update for dermatologists on the epidemiology, clinical presentation, diagnosis, and treatment of Mpox. The primary mode of transmission in the current outbreak is close physical contact during sexual activity. Although most of the initial cases were reported in men who have sex with men, anyone who has close contact with an infected person or contaminated fomites is at risk. Classic prodromal features of Mpox include subclinical manifestations and a mild rash. Complications are common but rarely require hospitalization. Polymerase chain reaction analysis of mucocutaneous lesions is the test of choice for a definitive diagnosis. In the absence of specific treatments, management focuses on symptomatic relief. Resumen: MPOX es una enfermedad zoonótica emergente que se ha propagado rápidamente por todo el mundo y que ha sido declarada por la OMS como una emergencia de salud pública de interés internacional. Esta es una revisión no sistemática de los aspectos clínicos, epidemiológicos, diagnósticos y terapéuticos más relevantes para el dermatólogo. En el brote actual, la transmisión durante las relaciones sexuales es la principal forma de contagio como resultado del contacto físico cercano. Si bien los casos iniciales se informaron en hombres que tienen sexo con hombres, cualquier persona en contacto cercano con personas o fómites infectados está en riesgo. El pródromo clásico puede ser subclínico y la erupción puede ser sutil. Las complicaciones son frecuentes, pero el requerimiento de hospitalización es infrecuente. El diagnóstico definitivo se realiza mediante PCR de las lesiones mucocutáneas. Actualmente no existen tratamientos específicos, y el tratamiento sintomático es el pilar terapéutico.